The quotient rule says that if $u$ and $v$ are functions of $x$ then
\[\simplify[std]{Diff(u/v,x,1)=(v * Diff(u,x,1) -(u * Diff(v,x,1))) / v ^ 2}\]
For this example:
\[\simplify[std]{u = {a} * x + {b}}\Rightarrow \simplify[std]{Diff(u,x,1) = {a}}\]
\[\simplify[std]{v = Sqrt({c} * x + {d})} \Rightarrow \simplify[std]{Diff(v,x,1) = {c} / (2 * Sqrt({c} * x + {d}))}\]
Hence on substituting into the quotient rule above we get:
\[\simplify[std]{Diff(f,x,1) = ({a} * Sqrt({c} * x + {d}) -(({a} * x + {b}) * Diff(v,x,1))) / ({c} * x + {d}) = ({a} * Sqrt({c} * x + {d}) -(({c} * ({a} * x + {b})) / (2 * Sqrt({c} * x + {d})))) / ({c} * x + {d}) = ({2 * a} * ({c} * x + {d}) -({c} * ({a} * x + {b}))) / (2 * ({c} * x + {d}) ^ (3 / 2)) = ({a * c} * x + {2 * a * d -(c * b)}) / (2 * ({c} * x + {d}) ^ (3 / 2))}\]
Hence \[\simplify[std]{g(x) = {a * c} * x + {2 * a * d -(c * b)}}\].